Interrelation Between Unionids and Their Epibionts in the Cooling Pond of the Khmelnitsky Nuclear Power Plant (Ukraine) - Sylayeva, A.A.; Protasov, A.A.; Morozovskaya, I.A. (Вестник зоологии, 2012)
Paper deals with data on interrelation of mollusks of the family Unionidae and Dreissena polymorpha (Pallas, 1771) and other epibiotic invertebrates in the cooling pond of the Khmelnitsky nuclear power plant (Ukraine). The quantitative indices of unionids and Dreissena, inhabiting shells of the living Unionidae, size structure of populations, and morphometric indexes of the living Unionidae were analyzed. No significant negative impact of settlements of the zebra mussels on Unionidae was noted. Приведены результаты исследований взаимоотношений между двустворчатыми моллюсками семейсва Unionidae, Dreissena polymorpha (Pallas, 1771) и другими эпибионтными беспозвоночными в водоёме-охладителе Хмельницкой АЭС (Украина). Проанализированы количественные показатели перловиц и дрейссены, обитающей на живых перловицах, размерная структура популяций моллюсков, морфометрические характеристики живых перловиц. Явно выраженного негативного влияния поселений дрейссены на перловиц не выявлено.